Perancangan Alat Produksi Tahu yang Higienis pada Industri Rumah Tangga - Anastasia Lidya Maukar; Johan K. Runtuk; Andira Andira (Jurnal Sistem dan Manajemen Industri, 2019)
Tofu industry dominates by small-scale business with traditional production methods. On the other hand, demand for tofu products is quite high, and it is needed to increase tofu production. This study discusses the making of hygiene tofu maker tools able to simplify the production process. Based on the results of interviews with three tofu home industries in Cikarang, Bekasi, 17 request attributes of making an assistive tool obtain. Based on this, four technical responses were collected and will be developed become four concept designs. After conducting concept selection, it is determined to plan for making a tool which can simplify the process of making tofu. That is, starting from the manufacturing process, which starts from the pulp to the process of making tofu, can be put together into one manufacture of the tool. Thus, designing this tool can integrate the six stages of the tofu production process.